دور الثقافة المتحفية في ترسيخ الهوية الثقافية - شكلاط, أميرة; بسقلال, نجاة (كلية الأدب العربي والفنون, 2024)
تلعب المتاحف دورا مهما في الحفاظ على الهوية الوطنية والثقافية من خلال ما تحتويه من تراث حضاري وثقافي متنوع، ونجد ان متاحف الجزائر لها دور محوري في الوحدة الوطنية وتعزيز الهوية الثقافية والحفاظ على المعلومات المتعلقة بالثقافة ونشرها في عالم شهد تغيرات غير عادية سياسيا واقتصاديا واجتماعيا، ففي أفريقيا اليوم، تدرک البلدان الدور الهام الذي تؤديه المتاحف في نشر المعرفة عن التراث الثقافي وإمکاناته في تعزيز التنوع الثقافي ، وبما أن المتاحف لها دور مهم في العلاقات الاجتماعية، فإنها تلعب دورا رئيسيا في تشکيل المشهد السياسي والثقافي المستقبلي لأفريقيا ککل والجزائر على وجه الخصوص. فالمتاحف هي مؤسسات الحفظ والترميم والبحث والعرض والتعليم. وعلى هذا النحو، تعتبر متاحف الجزائر موضوعا مثيرا للاهتمام وتستحق بحثا مستفيضا، على الرغم من محدودية البيانات. المتوفرة حولها، وبالتالي يهدف هذا البحث إلى معالجة وإلقاء بعض الضوء على المتاحف الجزائرية مع الترکيز على مجموعات المتاحف التاريخية والأثرية والاثنوغرافية والطبيعية والتي تبين أن المتاحف يمکن أن تکون أدوات ثقافية لتعزيز وحدتنا الوطنية وتعزيز التفاهم والوعي بالثقافات القديمة في الجزائر، وکذلك تعزيز الروابط مع المؤسسات الدولية الموازية، مثل المتاحف الأخرى في أفريقيا وخارجها، وتتمثل الأهداف الرئيسية للدراسة في لفت الانتباه إلى المتاحف الجزائرية ودورها الهام في التعليم والدراسات الاجتماعية والمجتمع والبحوث وغيرها Museums aimed at exploring in-depth how museums can help preserve national and cultural identity at the algeria Museums. The Role of Museums and Cultural Institutions in Strengthening Identity, was inaugurated by which aimed to stimulate meaningful dialogue about how museums can preserve and disseminate information about culture in a world that has seen extraordinary changes politically, economically and socially – largely as a result of globalisation. In Africa today, countries realise the important role museums play in dispersing knowledge about cultural heritage and its potential to promote cultural diversity and to heal ethnic divisions. Since museums have a formulative as well as a reflective role in social relations, they have a major role to play a major part in shaping the future political and cultural landscape of the new Africa. Museums are institutions of conservation, restoration, research, display and education. As such, Museums of the algeria are an interesting topic and deserve extensive investigation, despite data being very limited. This research aims to address in shedding some light on algeria museums with a focus on archaeological, ethnographic and natural history collections, showing that the museums can act as cultural tools, both to reinforce our national unity and to promote understanding and awareness of algeria ancient cultures in the algeria and abroad, and to promote links with parallel international institutions, such as other museums in Africa and beyond. The main objectives of the study areto draw attention to algeria museums and their important role in education, social studies, society, research, etc.
المتحف الولائي للمجاهد مستغانم أنموذجا
Keywords: المتاحف الجزائرية،المتاحف التاريخية والأثرية والاثنوغرافية